Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/onco.13890
|View full text |Cite
|
Sign up to set email alerts
|

Province-Wide Analysis of Patient-Reported Outcomes for Stage IV Non-Small Cell Lung Cancer

Abstract: Background. In Ontario, Canada, patient reported outcomes (PRO) evaluation through Edmonton Symptom Assessment System (ESAS) has been integrated into clinical workflow since 2007. As stage IV non-small cell lung cancer (NSCLC) is associated with substantial disease and treatment-related morbidity, this province-wide study investigated moderateto-severe symptom burden in this population. Methods. ESAS collected from stage IV NSCLC patients diagnosed between 2007-2018 linked to Ontario provincial healthcare syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…They reported that, although the severity of symptoms was low, the prevalence of specific symptoms such as tiredness, anxiety, pain and low wellbeing was high. In a similar study by Tjong et al 65 who assessed ESAS scores completed by 13,289 patients, they also observed that the most prevalent symptoms causing patient distress are tiredness, low wellbeing, low appetite and shortness of breath.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…They reported that, although the severity of symptoms was low, the prevalence of specific symptoms such as tiredness, anxiety, pain and low wellbeing was high. In a similar study by Tjong et al 65 who assessed ESAS scores completed by 13,289 patients, they also observed that the most prevalent symptoms causing patient distress are tiredness, low wellbeing, low appetite and shortness of breath.…”
Section: Discussionmentioning
confidence: 78%
“…This observation in the study is similar to what has also been reported in similar studies. 40,65 Cuthbert et al 40 conducted a retrospective, population-based cohort study on ESAS scores completed by 1,310 patients. They reported that, although the severity of symptoms was low, the prevalence of specific symptoms such as tiredness, anxiety, pain and low wellbeing was high.…”
Section: Discussionmentioning
confidence: 99%
“…First, a large proportion of patients were excluded as ESAS scores were not collected. As described previously, patients who did not complete any ESAS were more likely to be older, to have higher comorbidity and to not receive any active cancer treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall symptom burden using ESAS in stage IV NSCLC in Ontario has been previously reported by our research group, which found moderate-to-severe symptoms were prevalent and peaked at diagnosis while remaining high during the first year of follow-up [ 13 ]. The aim of the current study was to examine the intervention use and factors associated with interventions for pain (including palliative care assessment, radiation therapy, nerve block and opiate prescriptions) in stage IV NSCLC.…”
Section: Introductionmentioning
confidence: 86%
“…In this context, the problem of recurrent metastasis in NSCLC patients is crucial, as it causes detrimental rebounds not only on patients themselves and neoplasm prognosis, but also on caregivers, the healthcare system and society [ 4 ]. Unfortunately, despite the improved outcomes of metastatic NSCLC over the last decades, resulting from the introduction of combination chemotherapy, small molecules targeting mutant proteins, 5-year survival of these patients remains low, about 26% in stage IIIB, 10% in stage IVA and less than 1% in stage IVB patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%